Diagnostique spécifique - haricot commun - à Walungu - Musungayi, T; Sperling, L.; Graf, W; Lunze, Lubanga (International Center for Tropical Agriculture, 1992)
Common bean still is the basic food in the Walungu region and the almost only source of proteins. With farmers from Walungu in general and the women of the organisation Femmes solidaires pour le Développement du Bushi (FESODEBU) in particular, the team of the PNL/Mulungu has done a survey to define the problems and establish a participatory research program to improve bean production. Though female farmers acknowledge three cultural seasons, only one third of them believe to be self-sufficient in beans. They have noticed a yield decline over the last years, mentionning in particular low soil fertility and diseases as factors influencing bean yields. The results of the survey led the team to emphasize the following research subjects: 1) fertility (incorporation of green manure, improved management of manure and compost, breeding of varieties tolerant to low soil fertility); 2) high-performance varieties (bush and climbers); 3) seed (multiplication in farmers` fields and improvement of diffusion channels).